Behavioral and socio-economic determinants of urban households’ investment in energy efficient technologies: evidence from Ethiopia - Hassen, Sied; Anandarajah, Gabrial; Seifemichael, Robel (Frontiers in Energy Research, 2023)
Wide uses of energy-efficient technologies have the potential to save a significant amount of electricity, which may allow deferral of construction of new power plants. However, in low-income countries, there is low use of energy-efficient technologies. This paper studies the behavioral and socio-economic determinants of urban households’ investment in energy efficiency improvements in Ethiopia. It considers multiple technologies and uses a multivariate probit model to take into account the sequential or simultaneous adoption of energy-efficient technologies. Using a random sample of 1400 urban households from nine regions in Ethiopia, the study finds that most households (86%) adopt energy-efficient technologies and other energy conservation activities mainly to reduce energy expenses. Interestingly, at least 12% of the respondents adopt these activities out of concern for the environment and future generations, which is encouraging. The multivariate probit regression result shows that households’ educational status, income or occupational status, access to credit, and age are significant determinants of households’ investment on energy-efficient technologies. In contrast to many rural studies on energy efficient technologies, gender is not a significant determinant for the adoption of energy-efficient technologies, as both husband and wife have an incentive to save cost of energy. The results have implications on a need for a policy that incentivizes or promotes firms to sell energy-efficient products on installment (credit) and also a policy on the language of product specifications.